Monitoring changes of the Antarctic Ice sheet by GRACE, ICESat and GNSS - Zou, F; Tenzer, R; Rathnayake, S (Contributions to Geophysics and Geodesy, 2019)
In this study, we estimate the ice mass changes, the ice elevation changes and the vertical displacements in Antarctica based on analysis of multi-geodetic datasets that involve the satellite gravimetry (GRACE), the satellite altimetry (ICESat) and the global navigation satellite systems (GNSS). According to our estimates, the total mass change of the Antarctic ice sheet from GRACE data is -162.91 Gt/yr over the investigated period between April 2002 and June 2017. This value was obtained after applying the GIA correction of -98.12 Gt/yr derived from the ICE-5G model of the glacial isostatic adjustment. A more detailed analysis of mass balance changes for three individual drainage regions in Antarctica reveal that the mass loss of the West Antarctic ice sheet was at a rate of - 143.11 Gt/yr. The mass loss of the Antarctic Peninsula ice sheet was at a rate of -24.31 Gt/yr. The mass of the East Antarctic ice sheet increased at a rate of 5.29 Gt/yr during the investigated period. When integrated over the entire Antarctic ice sheet, average rates of ice elevation changes over the period from March 2003 to October 2009 derived from ICESat data represent the loss of total ice volume of -155.6 km(3). The most prominent features in ice volume changes in Antarctica are characterized by a strong dynamic thinning and ice mass loss in the Amundsen Sea Embayment that is part of the West Antarctic ice sheet. In contrast, coastal regions between Dronning Maud Land and Enderby Land exhibit a minor ice increase, while a minor ice mass loss is observed in Wilkes Land. The vertical load displacement rates estimated from GRACE and GPS data relatively closely agree with the GIA model derived based on the ice-load history and the viscosity profile. For most sites, the GRACE signal appears to be in phase and has the same amplitude as that obtained from the GPS vertical motions while other sites exhibit some substantial differences possibly attributed to thermo-elastic deformations associated with surface temperature. Department of Land Surveying and Geo-Informatics 202006 bcrc published_final